Dynamics of clinical and laboratory indicators in serious patients and deaths with new coronavirus infection of COVID-19 under treatment of 8 mg dexamethasone - V.I. Trykhlib; T.I. Lysenko; A.O. Yeroshenko; О.S. Martynchuk; K.P. Bieliaieva; N.R. Tsiurak; T.I. Shevelova; S.S. Popova; S.M. Samoilova; S.M. Chaika; O.S. Holubenko; А.V. Moroz (Aktualʹnaâ Infektologiâ, 2021)
The article provides a review of the literature on the effectiveness of glucocorticoids in viral infections, including the new coronavirus infection COVID-19. The results of our research of the dynamics of laboratory parameters in patients who recovered and those who died are presented. The average age of patients who received 8 mg of dexamethasone and recovered was less than that of the deceased. The average day on which the patients were hospitalized in the ICU and who received 8 mg of dexamethasone in both groups was the same (on average on day 7). It is noteworthy that in patients who recovered, the febrile temperature was more often recorded before hospitalization, while in those who died it was more often subfebrile. The temperature during hospitalization in all categories of patients was on average at subfebrile numbers. The respiratory rate on admission in all categories of patients did not differ significantly and on average was about 19/min (up to 20/min was in 50 % of patients who recovered and 58.3 % of those who died). Those who recovered were more likely to have a normal heart rate on admission, but tachycardia was less common than within those who died. In patients who subsequently died, lower saturation levels were more often recorded upon admission. In the first 3 days after hospitalization, in patients who recovered and received 8 mg of dexamethasone, leukocytosis and granulocytosis were recorded more often; there was an increased number of stab neutrophils and the number of patients with it. The patients who subsequently died more often developed leukopenia, more pronounced lymphopenia with an increased quantity of patients with it; they presented more pronounced thrombocytopenia (the number of patients with it did not differ from those who recovered), higher erythrocyte sedation rate. In patients who subsequently died, during the observation period, there was a gradual increase in the number of leukocytes, but a gradual decrease in the number of lymphocytes, the creatine phosphokinase level increased from the 7th–9th days of hospitalization; on days 4–6 of hospitalization, the lactate dehydrogenase level significantly increased with its subsequent decline to a level that was greater than this in patients who recovered. Initially. The patients who recovered had an increase in leukocytes with their subsequent gradual decrease, a gradual increase in the level of lymphocytes, a decrease in the level of creatine phosphokinase, lactate dehydrogenase. In all categories of patients, a gradual decrease in the number of stab neutrophils was observed over time, a gradual increase in the number of platelets was also observed over time, but in those who recovered their level was slightly higher; in both groups, an increase in the urea level was observed over time, but in those who died its level from day 7 and later was significantly higher than in those who recovered; in patients in both groups, an increase in the level of creatinine was observed over time, but in those who died, its level from day 7 and later was significantly higher than in those who recovered; both groups showed a decrease in C-reactive protein over time, but those who died from the very beginning of their hospital stay and during all follow-up periods had higher levels than those who recovered.